Pengaruh Model Pembelajaran Cooperative Script terhadap Hasil Belajar Siswa dalam Mata Pelajaran Seni Budaya (Tari) Kelas IX di SMP N 2 Padang - Yolanda Asih Amalia; Yuliasma Yuliasma (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to determine and describe the influence of student dance learning outcomes taught using the Cooperative Script learning model with the learning outcomes of students taught using the Conventional model in cultural arts learning at SMPN 2 Padang. This type of research is quantitative research with a quasi-experimental approach. The population in this study was all students in grade IX SMP N 2 Padang, totaling 242 students with samples using purposive random sampling. The research instrument uses pre-test and post test. Data were collected through observation, documentation and cognitive tests. Data were analyzed using normality test, homogeneity test, hypothesis test and independent test. The results showed that there was a significant difference between student learning outcomes before and after applying the Cooperative Script model. The increase in learning outcomes in the group using the Cooperative Script model was the average learning outcome from pretest (69.47) to posttest (87.80). In the group using the conventional model, the average increase in learning outcomes from pretest (69.33) to posttest (77.23). It can be seen that the experimental class using the Cooperative Script Model has a better performance compared to the control class for SMPN 2 Padang students, this can be seen from the average value on the experimental posttest is greater than the average posttest control which means there is a significant influence in using the Cooperative Script Model.